2023
DOI: 10.1007/s12672-023-00615-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor infiltrating lymphocytes on first-line pembrolizumab efficacy in advanced non-small cell lung cancer

Abstract: Aim Tumor-infiltrating lymphocytes (TILs) in the tumor and stroma are expected to accurately predict the efficacy of programmed death-1 (PD-1) blockade therapy. However, little is known about the prognostic significance of TILs in first-line PD-1 therapy. We assessed TILs in patients with advanced or metastatic non-small cell lung cancer (NSCLC) treated with pembrolizumab in the palliative setting. Methods Multiplex immunohistochemistry staining of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In general, ICIs promote the entry of CD4, CD8, and other tumor‐infiltrating lymphocytes (TILs) into tumors, where they subsequently kill tumor cells 19 . Angiogenetic proteins such as vascular endothelial growth factor (VEGF) and VEGFR create an immunosuppressive tumor microenvironment, with resultant increases in the expression of FOXP3 and the number of myeloid‐derived suppressor cells 20–22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, ICIs promote the entry of CD4, CD8, and other tumor‐infiltrating lymphocytes (TILs) into tumors, where they subsequently kill tumor cells 19 . Angiogenetic proteins such as vascular endothelial growth factor (VEGF) and VEGFR create an immunosuppressive tumor microenvironment, with resultant increases in the expression of FOXP3 and the number of myeloid‐derived suppressor cells 20–22 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, ICIs promote the entry of CD4, CD8, and other tumor‐infiltrating lymphocytes (TILs) into tumors, where they subsequently kill tumor cells. 19 Angiogenetic proteins such as vascular endothelial growth factor (VEGF) and VEGFR create an immunosuppressive tumor microenvironment, with resultant increases in the expression of FOXP3 and the number of myeloid‐derived suppressor cells. 20 , 21 , 22 We hypothesize that extended ICI treatment achieves a tumor microenvironment in which CD4/CD8 TIL levels are high and FOXP3 levels are low, contributing to the downregulation of VEGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another multicenter cohort study in dMMR mCRC patients illustrates that low levels of peripheral CD4+T cells and CD4+/CD8+ ratio could be positive independent potential biomarkers for predicting survival outcomes, 117 further supporting the critical role of CD4+T cells in promoting CD8+ T cells antitumor activities. And by a recent clinicopathological study indicated CD4 in the stroma was consistently associated with PD‐L1 in 50% of the patients; however, the CD8 in intratumoral lesions was associated with PD‐L1 in 1−49% 118 . Despite this, it is unclear if CD4+ T cells with PD‐L1 expression correlate with prognosis after first‐line anti‐PD‐1 treatment.…”
Section: Circulating Immune Cells In Antitumor Immunotherapymentioning
confidence: 97%
“…However, PBMCs are less predictive compared to tumor-infiltrated immune cells. As tumor-infiltrated immune cells are in contact with tumoral cells, a predictive value of these cells has been assigned to immunotherapy responses ( 13 ). For example, for non-responders to immunotherapy, an increased proportion of myeloid-derived suppressor cells (MDSCs), and a decreased proportion of natural killer (NK) cells, and monocytes in the tumor site constitute an immunosuppressive microenvironment.…”
Section: Introductionmentioning
confidence: 99%